Perilaku Pencarian Informasi dan Kemampuan Mahasiswa Menulis Pendahuluan Penelitian: Studi Kasus Mata Kuliah Chinese Scientific Writing - Ernawati, Endang (Humaniora, 2011)
Article clarified students’ behaviors in seeking and searching information to support their researches, especially in formulating topics, problems, and goals of researches. Qualitative method was applied to forty three students from the Chinese Departments as respondents. They took Chinese Scientific Writing subject in BINUS University at the odd semester in 2010-2011. The observation of students’ behavior to access information was conducted in one week because it is a preliminary research for the advanced one. Analysis was done by evaluating students’ assignments on their proposals that was submitted at the end of semester, especially on the formulation of researches’ topics, problem formulation, and goals of researches. It is concluded that only twenty students (46.51 %) who are able to compose background of research properly, it means that they are able to express their interest on the researches’ topics, and this abilities have a positive correlation on their ability in formulating researches’ problems and goals.